2022
DOI: 10.1038/s41598-022-05731-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression ratio of circular to linear ANRIL in hypertensive patients with coronary artery disease

Abstract: Atherosclerotic lesions of the coronary arteries are still in charge of significant annual morbidity and mortality despite intense therapeutic advancements. Genome-born elements contribute substantially to the atherosclerosis process. ANRIL is one of the long non-coding RNAs with outstanding functions particularly regulation of genes involved in atherosclerosis development. In this study, we measured ANRIL expression (circular-, linear-, and circular/linear ratio) in hypertensive patients with coronary artery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 50 publications
(86 reference statements)
0
7
0
Order By: Relevance
“…The regulation of the balance depends on the cell type and context, however, there is still no sufficient data on the molecular coordinator of the ratio of linear and circular isoforms, and it is not known whether inhibition of linear ANRIL isoforms is sufficient to protect against CHD and DM2. [ 30 ] Perhaps this special influence of ANRIL can also explain the paradox when the genes involved in the biology of traits show different effects. Genetic variants can disrupt ANRIL, which mechanically links CHD to DM2.…”
Section: Resultsmentioning
confidence: 99%
“…The regulation of the balance depends on the cell type and context, however, there is still no sufficient data on the molecular coordinator of the ratio of linear and circular isoforms, and it is not known whether inhibition of linear ANRIL isoforms is sufficient to protect against CHD and DM2. [ 30 ] Perhaps this special influence of ANRIL can also explain the paradox when the genes involved in the biology of traits show different effects. Genetic variants can disrupt ANRIL, which mechanically links CHD to DM2.…”
Section: Resultsmentioning
confidence: 99%
“…CDKN2B-AS1 plays a vital role in cell proliferation, aging, inflammation, apoptosis and also as a tumor suppressor [ 34 , 35 ]. In the field of cardiovascular disease, CDKN2B-AS1 has been associated with atherosclerotic vascular disease, coronary artery disease, stroke, aortic aneurysm, and myocardial infarction [ 36 ]. Vausort et al [ 13 ] showed that patients with ST-segment-elevation AMI had significant lower levels of CDKN2B-AS1 than patients with NSTEMI (P<0.001).…”
Section: Discussionmentioning
confidence: 99%
“…CircRNAs can act as competitive endogenous RNA (ceRNA) by sequestering one or multiple RNA-binding proteins (RBP) or miRNAs [ 82 ]. Analysis of the ratio between circular and linear ANRIL isoforms within a cohort of patients with CVD and melanoma revealed a significant difference compared to the control groups [ 78 , 83 ]. In addition, Holdt and colleagues discovered a circANRIL, which exhibits anti-atherosclerotic properties by sequestrating PES1, a factor involved in the assembly of the 60S ribosomal subunit.…”
Section: Anril Exons and Isoformsmentioning
confidence: 99%